Efficacy of Intermittent or Continuous Very Low-Energy Diets in Overweight and Obese Individuals with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analyses - Yi Shan Huang; Qiyan Zheng; Huisheng Yang; Xinwen Fu; Xueqin Zhang; Chenhui Xia; Zebing Zhu; Yu Ning Liu; Wei Jing Liu (Journal of Diabetes Research)
Objective. This study is aimed at investigating the efficacy of a very low-energy diet (VLED) in overweight and obese individuals with type 2 diabetes mellitus (T2DM). Methods. We thoroughly searched eight electronic resource databases of controlled studies concerning the efficacy and acceptability of intermittent or continuous VLEDs in patients with T2DM compared with other energy restriction interventions. Results. Eighteen studies (11 randomized and seven nonrandomized controlled trials) with 911 participants were included. The meta-analyses showed that compared with a low-energy diet (LED) and mild energy restriction (MER), VLED is superior in the reduction of body weight (mean difference (MD) MDLED=−2.77, 95% confidence interval (CI) CILED=−4.81 to−0.72, PLED=0.008; MDMER=−6.72, 95%CIMER=−10.05 to−3.39, PMER<0.0001), blood glucose (MDLED=−1.18, 95%CILED=−2.05 to−0.30, PLED=0.008; MDMER=−6.72, 95%CIMER=−10.05 to−3.39, PMER<0.0001), and triglyceride (TG) (MDLED=−0.35, 95%CILED=−0.58 to−0.12, PLED=0.002; MDMER=−0.55, 95%CIMER=−0.93 to−0.17, PMER=0.005) levels at the end of the intervention. After the follow-up (1–5 years), no obvious difference in weight loss (MD=−0.84, 95%CI=−3.01 to 1.32, P=0.45, I2=0%) and TG level (MD=−0.25, 95%CI=−0.55 to 0.06, P=0.12, I2=0%) between VLEDs and LEDs was evident, but VLED is more effective in glycemic control (MD=−1.43, 95%CI=−2.65 to−0.20, P=0.02). Compared to bariatric surgery, VLEDs offered comparable effects on weight loss (MD=2.51, 95%CI=−9.52 to 14.54, P=0.37), glycemic control (MD=0.37, 95%CI=−0.22 to 0.96, P=0.22), TG (MD=−0.3, 95%CI=−0.74 to 0.17, P=0.7), and insulin resistance improvement (MD=−1, 95%CI=−2.7 to 0.7, P=0.25). Conclusion. Dietary intervention through VLEDs is an effective therapy for rapid weight loss, glycemic control, and improved lipid metabolism in overweight and obese individuals with T2DM. Thus, VLEDs should be encouraged in overweight and obese individuals with T2DM who urgently need weight loss and are unsuitable or unwilling to undergo surgery. As all outcome indicators have low or extremely low quality after GRADE evaluation, further clinical trials that focus on the remission effect of VLEDs on T2DM are needed.